PENGUJIAN DAUN JERUK PURUT (Citrus hystrix) SEBAGAI ZAT PENOLAK ALAMI BAGI KECOA JERMAN (Blatella germanica) DEWASA DI LABORATORIUM - Amin, Ika Dina; Hestiningsih, Retno; Yuliawati, Sri (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
The use of synthetic insecticides already caused resistance, pest resurgence and ecosystem disruption. Alternative way is using Kaffir lime leaves (Citrus hystrix), it can be used as a natural insecticides as it’s contain repellent that useful to repel cockroach. Blatella germanica is a cockroach spesies we usually see in our neighbourhood, so that we have to control this cockroach. The purpose of this research is to measure the ability of young kaffir lime leaves with the old one. This research use the experimental research method in laboratory with complete random research design. Sample of this research are 280 mature Blatella germanica age 1,5-4 months old which has complete body structure. This research use 3 typhes of stages and 9 times repetitions. We could say that kaffir lime leaves is effective as repellent if it has protection power level more than 80%. According to the research there is a result of an effective dosage of kaffir lime leaves as a repellent is 5 grams of old or young leaves with 81,8%, the protection ability of old kaffir lime leaves bigger than the young leaves bigger and the ability to repel Blatella germanica for three days so that kaffir lime leaves can be used as a natural repellent to repel Blatella germanica. The use of kaffir lime leaves can be socialized by related instution and the community can grow kaffir lime around their neighbourhood as a cockroach repellent.